2021
DOI: 10.1177/23328584211028601
|View full text |Cite
|
Sign up to set email alerts
|

One Program Fits All? Patterns and Outcomes of Professional Development During a Large-Scale Reform in a High-Stakes Science Curriculum

Abstract: When translating large-scale policy changes into educational practice, classroom-level implementation is crucial and dependent on teachers’ capabilities. Most research underscores the importance of professional development (PD) as a proximal factor to achieve educational change. Connected to the recent Advanced Placement (AP) science examination reform, this large-scale quantitative study (NTeachers = 9,096; NStudents = 197,589) investigates teacher participation in different PD formats (i.e., face-to-face, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
(97 reference statements)
0
4
0
Order By: Relevance
“…Research suggests that activities spread over time, such as semesterlong courses with 20 or more hours of contact time, are beneficial for teacher development [22], [24]. From this viewpoint, some professional development programs adhere more closely with the idea of lifelong learning compared to programs that only last a few days each school year [34].…”
Section: Key Features Of Teacher Professional Development In Financia...mentioning
confidence: 99%
“…Research suggests that activities spread over time, such as semesterlong courses with 20 or more hours of contact time, are beneficial for teacher development [22], [24]. From this viewpoint, some professional development programs adhere more closely with the idea of lifelong learning compared to programs that only last a few days each school year [34].…”
Section: Key Features Of Teacher Professional Development In Financia...mentioning
confidence: 99%
“…Teachers who participate in intercultural professional development related to cultural diversity and who decide to work or study abroad may share certain characteristics, such as having higher intercultural self-efficacy from the start. Some studies found selection effects with regards to participation in professional development or study abroad programs (Hübner et al, 2021;Zimmermann et al, 2020), while others did not (Petersdotter et al, 2017). Similarly, higher teacher intercultural self-efficacy in schools with a higher proportion of first-and second-generation immigrant students may also indicate selfselection effects, i.e., teachers with higher intercultural self-efficacy choosing to work at more diverse schools.…”
Section: Limitations and Suggestions For Future Researchmentioning
confidence: 99%
“…This study is tied to a large-scale National Science Foundation-project that broadly examined teachers' PD participation patterns and their impact on classroom instruction and student performance, which distributed web-based surveys to all AP Biology teachers in the nation (e.g., Fischer et al, 2018;Fischer, Foster, et al, 2020;Hübner et al, 2021). Surprisingly at the time, we found that many AP Biology teachers reported their engagement in Twitter communities as an informal learning opportunity on an open-response question on their online activities in response to the AP reform.…”
Section: Study Contextmentioning
confidence: 99%